Direct immunogold labeling of aquaporin-4 in square arrays of astrocyte and ependymocyte plasma membranes in rat brain and spinal cord - Rash, John E. (National Academy of Sciences, 1998)
Aquaporin (AQP) water channels are abundant in the brain and spinal cord, where AQP1 and AQP4 are believed to play major roles in water metabolism and osmoregulation. Immunocytochemical analysis of the brain recently revealed that AQP4 has a highly polarized distribution, with marked expression in astrocyte end-feet that surround capillaries and form the glia limitans; however, the structural organization of AQP4 has remained unknown. In freeze-fracture replicas, astrocyte end-feet contain abundant square arrays of intramembrane particles that parallel the distribution of AQP4. To determine whether astrocyte and ependymocyte square arrays contain AQP4, we employed immunogold labeling of SDS-washed freeze-fracture replicas and stereoscopic confirmation of tissue binding. Antibodies to AQP4 directly labeled ≈33% of square arrays in astrocyte and ependymocyte plasma membranes in rat brain and spinal cord. Overall, 84% of labels were present beneath square arrays; 11% were beneath particle clusters that resembled square arrays that had been altered during fixation or cleaving; and 5% were beneath the much larger areas of glial plasma membrane that were devoid of square arrays. Based on this evidence that AQP4 is concentrated in glial square arrays, freeze-fracture methods may now provide biophysical insights regarding neuropathological states in which abnormal fluid shifts are accompanied by alterations in the aggregation state or the molecular architecture of square arrays.